Visual Iconicity Across Sign Languages: Large-Scale Automated Video Analysis of Iconic Articulators and Locations - Östling, Robert; Börstell, Carl; Courtaux, Servane (Frontiers in Psychology, 2018)
We use automatic processing of 120 000 sign videos in 31 different sign languages to show a cross-linguistic pattern for two types of form--meaning relationships in the visual modality. First, we demonstrate that the degree of inherent plurality of concepts, based on individual ratings by non-signers, strongly correlates with the number of hands used in the sign forms encoding the same concepts across sign languages. Second, we show that the semantics of a concept is strongly associated with its place of articulation in a way predicted by non-signers' intuitions. The implications of our results are both theoretical and methodological. With regard to theoretical implications, we corroborate previous research by demonstrating and quantifying, using a much larger material than previously available, the iconic nature of languages in the visual modality. As for the methodological implications, we show how automatic methods are, in fact, useful for performing large-scale analysis of sign language data, to a high level of accuracy, as indicated by our manual error analysis.